FEATURES OF THE SPREAD OF ALLERGIC DISEASES IN CHILDREN (Neo Scientific Peer Reviewed Journal, 2025)
The prevalence of asthma symptoms was studied by questionnaire screening using the adapted international ISAAC questionnaire among 1250 school-age children in two age groups – 7-8 years old (parents of children were surveyed) and 13-14 years old (children were surveyed) in the Turakurgan , Chust districts of the Namangan region, as well as in the city of Namangan, the Republic of Uzbekistan.